2021
DOI: 10.2147/jmdh.s309938
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pharmacists in the Interprofessional Care Team for Patients with Chronic Diseases

Abstract: Chronic diseases are a major health problem and cause of death worldwide. Patients with chronic diseases should be managed by an interprofessional care team consisting of general practitioners, medical specialists, nurses, and pharmacists. However, the roles of pharmacists in this interprofessional care team have not been fully explored. This study, therefore, examined their roles as members of the interprofessional care team in managing patients with chronic diseases. A search in PubMed, Google Scholar, EBSCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 41 publications
0
32
0
2
Order By: Relevance
“…Pharmacists can help build adherence strategies for non-compliant patients. 13 4 Clinical ward round participation in specialty units of the hospital Clinical pharmacists may participate in clinical ward rounds in the medical and nursing staff team and monitor the therapy measures of patients. During active ward rounds, they can document detailed information and advice on medication provided to and help set the therapeutic goals, reduce preventable adverse drug events (ADEs), provide drug information, and aid in optimizing drug therapy.…”
Section: Potential Areas For Pharmd Graduates In Hospitals Of Nepalmentioning
confidence: 99%
“…Pharmacists can help build adherence strategies for non-compliant patients. 13 4 Clinical ward round participation in specialty units of the hospital Clinical pharmacists may participate in clinical ward rounds in the medical and nursing staff team and monitor the therapy measures of patients. During active ward rounds, they can document detailed information and advice on medication provided to and help set the therapeutic goals, reduce preventable adverse drug events (ADEs), provide drug information, and aid in optimizing drug therapy.…”
Section: Potential Areas For Pharmd Graduates In Hospitals Of Nepalmentioning
confidence: 99%
“…Pharmacists were reported to have higher barriers in collaboration than nurses because of limited doctor and nurse knowledge about the pharmacists' competencies. Pharmacists possess clinical skills [30,31] and not only skills in drug management and procurement [32]. Another barrier to collaboration that has been reported between physicians and pharmacists is communication, lack of specific collaboration rules (standards of cooperation), self-confidence, low mutual respect, and trust [31].…”
Section: Profession Influences Cpat Perceptionmentioning
confidence: 99%
“…[7][8][9][10][11] The collaboration between pharmacists and health professionals in primary care clinics plays an important role in medicine management services. 12 13 Some studies have explored the satisfaction and effectiveness of incorporating pharmacist services into primary care clinics, reporting favourable results in the management of chronic diseases and quality use of medications. 8 Prior studies have shown that the number of patient risk-factors for medication-related problems decreased significantly after the…”
Section: Introductionmentioning
confidence: 99%